Design and performance evaluation of multilevel inverter for solar energy systems and electric vehicle charging with multi output active clamp forward converter - Adupa Chandramouli; Siva Chidambaranathan V. (Science and Technology for Energy Transition)
This paper addresses the challenges of achieving efficient and high-quality power conversion in solar energy systems and electric vehicle (EV) charging applications by introducing a Multi-Output Active Clamp Forward Converter (MOACFC). The proposed system is designed to generate symmetrical and asymmetrical DC voltage configurations for a Multilevel Inverter (MLI) topology. Traditional MLI topologies often require numerous switches and DC sources, leading to increased complexity and reduced efficiency. To overcome these limitations, the MOACFC delivers multiple output voltages from a single solar generation input, effectively reducing the number of switches and DC sources required. This study also highlights the application of a Recurrent Neural Network Incremental Conductance (RNN-INC)-based Maximum Power Point Tracking (MPPT) algorithm to optimize power extraction from photovoltaic (PV) arrays. The MLI system’s fundamental module can produce 9-level, 21-level, and 31-level outputs, with the Nearest Level Control Pulse Width Modulation (NLCPWM) and Level Shifted Pulse Width Modulation (LSPWM) techniques employed to minimize Total Harmonic Distortion (THD). The results demonstrate significant improvements in power quality, with THD levels reduced to 3.77% in voltage and 0.99% in current for EV charging applications – substantially better than conventional 2-level and 3-level inverters. The findings indicate that the proposed MOACFC-MLI system is a more efficient and reliable alternative, offering enhanced power quality and reduced electrical stress on EV battery systems.